Influences of anthropogenic activities on water quality in the Saigon River, Ho Chi Minh City. (14th February 2022) - Thai-Hoang, Le; Thong, Truong; Loc, Hoang Thai; Van, Pham Thi Trang; Thuy, Pham Thi Phuong; Thuoc, Tran Linh
Abstract: Water quality for the surface water along the Saigon River in Ho Chi Minh City was assessed for four groups of water samples collected at the agricultural, industrial, residential, and less impacted areas. A variety of parameters indicating water quality including physicochemical parameters, nutrients, heavy metals, and antibiotic residues were measured for both the rainy and dry seasons, two main tropical seasons in HCM City using the standard methods. The results showed that the river water in the rainy season was detected with significantly higher values of turbidity, BOD5, PO4 -P, NH4 -N, NO3 -N; and lower values of pH, temperature, conductivity, DO, salinity, Cu, Zn, As, Ni, Hg compared to that in the dry season. Sulfamethoxazole and trimethoprim were highly detected in the industrial areas compared to the agricultural and residential areas. Multivariate analyses suggested that the industrial and residential activities were more important contributors to the pollution of the Saigon River than the agricultural activities in HCM City. HIGHLIGHTS: The occurrences of nutrients, heavy metals, and selected antibiotics in the Saigon River were different between the dry and rainy seasons. Industrial and residential activities were found to be more important contributors to the contamination in the Saigon River in comparison to the agricultural activities. The highly polluted sites in the Saigon River were impacted by both industrial and residential activities. Graphical Abstract